Ideas: Education for migrants: An inalienable human right - Fons Coomans (The UNESCO Courier, 2019)
The right to education is often taken for granted – until it is taken away. An indispensable tool to protect the freedom and dignity of all migrants, education allows them to fully integrate into their new societies. This legitimate aspiration, however, faces obstacles on the ground.